Kelembagaan Badan Usaha Milik Desa di Kabupaten Buton Selatan - Zainul Abidin; La Didi; Rahmawati Rahmawati; Firman Akbar (PERSPEKTIF, 2022)
The purpose of this study is to describe the institutions of Village-Owned Enterprises in South Buton Regency. This research is important to do because there are several problems including the application of rules and management of Village-Owned Enterprises that are not appropriate and lack of internal control. The research design used was qualitative with a descriptive approach. Data were collected using observation techniques, interviews and also through document review. The data were analyzed using an interactive model. The results of this study reveal that the implementation of village-owned enterprises in South Buton Regency is limited with various problems. From the regulatory aspect, it has been based on rules such as village regulations, management decrees and AD/ART, but there are some villages that are constrained by legalization due to internal problems. Meanwhile, from the normative aspect, the evaluation form and the accountability model for the management of Village-Owned Enterprises have not been carried out properly because there are still unaccountable management reports. However, there are several efforts by the Village Community Empowerment Service (DPMD) along with Community Empowerment Experts to help overcome finding solutions. As a result, one of the villages, namely Lampanairi village, succeeded in encouraging the role of its Village-Owned Enterprises and became a driving force for the community's economy and was part of 125 villages that received the title of Brilliant Village in the category of economic business development village in the midst of the Covid 19 pandemic.